Traditionalist salafi’s involvement in the religious moderation da’wah - Hafiz Muhammad Farooq Abdullah; Lukmanul Hakim; M. Syahidan (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
Traditionalist Salafi groups differ from political and jihadist salafi groups. Traditionalist Salafi chose a moderate path in their preaching. This article aims to analyze the moderate path of Salafi Rodja in Indonesia. Using a qualitative method where data is collected through observation and reading the community's official website and interviewing key informants, we argue that Rodja as a traditionalist salafi in Indonesia develops a moderate way of preaching by applying two approaches. First, contextualizing the understanding of jihad by rejecting violence in the name of Islamic jihad. Second, engage in social activities by providing educational services and moral and material assistance to people in need. Both of these approaches show the humanization of salafi teachings which are usually associated with extremism. This fact shows that Indonesian traditionalist Salafi seeks to emphasize moderate and humanist religious ways in their preaching. However, the tendency to moderate the way (manhaj) of da'wah cannot be separated from its position as a breakaway among mainstream moderate Islamic groups (Nahdlatul Ulama and Muhammadiyah), in addition to the government's efforts to eradicate extremist movements. This study contributes to the strengthening of moderate da'wah discourse among splinter groups***Kelompok Salafi tradisionalis berbeda dengan kelompok Salafi politik dan jihadis. Salafi tradisionalis memilih jalan moderate dalam dakwahnya. Artikel ini bertujuan untuk menganalisis jalur moderat Salafi Rodja di Indonesia. Dengan menggunakan metode kualitatif di mana data dikumpulkan melalui observasi dan membaca website resmi komunitas serta mewawancarai informan kunci, kami berpendapat bahwa Rodja sebagai salafi tradisionalis di Indonesia mengembangkan cara dakwah moderat dengan menerapkan dua pendekatan. Pertama, mengkontekstualisasikan pemahaman jihad dengan menolak kekerasan atas nama jihad Islam. Kedua, terlibat dalam kegiatan sosial dengan menyediakan layanan pendidikan dan bantuan moril dan material kepada masyarakat yang membutuhkan. Kedua pendekatan ini menunjukkan humanisasi ajaran salafi yang biasanya sering diasosiasikan dengan ekstremisme. Fakta ini menunjukkan bahwa Salafi tradisionalis Indonesia berusaha untuk menekankan cara-cara keagamaan yang moderat dan humanis dalam dakwahnya. Namun, kecenderungan untuk memoderasi cara (manhaj) dakwah tidak lepas dari posisinya sebagai sempalan di antara kelompok arus utama Islam moderat (Nahdlatul Ulama dan Muhammadiyah), di samping upaya pemerintah memberantas gerakan ekstremis. Studi ini memberikan kontribusi bagi penguatan diskursus dakwah moderat dalam kalangan kelompok sempalan.